Investigation of Daily Natural and Rapid Human Effects on the Air Temperature of The Hajnóczy Cave in Bükk Mountains - Muladi, Beáta; Mucsi, László (Journal of Environmental Geography, 2013)
The aim of this study the authors measured and analyzed the effect of the exterior daily temperature change on the interior temperature in a dripstone cave visited by cavers exclusively. The measurement was carried out in the Hajnóczy Cave located in the southern part of Bükk Mountains in Hungary. Although only one entrance is known, there are more evidences for the strong effect of exterior conditions on the interior processes like temperature fluctuation and dripstone development. Using high resolution wireless digital thermometer sensor network the air temperature and air humidity were measured in 32 points in every 10 minutes for long time but now the data of a 8-days period were analyzed. Based on these data different zones of the cave could be separated and during summer conditions the climatic variability of the entrance transitional and deep cave zone was described. Based on statistical analysis of spatial information significant correlation was found between the exterior temperature fluctuation and that of such a cave chamber, which is relatively far from the cave entrance. This fact proves that existence of a fissure system which is permeable for air but not passable for cavers. During the measurement the human effect was also analyzed and 0.3-0.6 °C temperature rising was recognized for a short time. Because of the surface vicinity the effects of the environmental change can have sensible impact on the cave and its natural phenomena. Among others temperature rising, air humidity decreasing were detected in present study.